2007
DOI: 10.1159/000106584
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab for the Treatment of Disseminated Pyoderma Gangrenosum Associated with Ulcerative Colitis

Abstract: We report the case of a 19-year-old woman who developed an acute disseminated pyoderma gangrenosum (PG) during a severe flare of ulcerative colitis (UC). She was successfully treated with a 3-dose regimen of the anti-tumor-necrosis-factor-α antibody infliximab. The literature on the effectiveness of this biological agent was reviewed, including 8 other cases of UC-associated PG and 77 cases of Crohn’s-disease-associated PG. This case report and the review of the literature demonstrate that infliximab can be su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 148 publications
2
29
1
2
Order By: Relevance
“…Many reports regarding the successful use of infliximab for PG (10) are in contrast with two reported cases (including ours) of PG onset during anti-TNF-a therapy (II). Although PG has been widely reported with IBD (10), its onset during infliximab therapy is again a paradox.…”
Section: Discussioncontrasting
confidence: 73%
“…Many reports regarding the successful use of infliximab for PG (10) are in contrast with two reported cases (including ours) of PG onset during anti-TNF-a therapy (II). Although PG has been widely reported with IBD (10), its onset during infliximab therapy is again a paradox.…”
Section: Discussioncontrasting
confidence: 73%
“…Table 1 summarizes the published cases of acute and/or severe ABD treated with IFX and shows how satisfactory the response to the TNF-␣ inhibitor is, with 76/99 patients experiencing complete remission, 15 patients with partial remission and only 8 patients showing no response. Further, IFX has also been reported as a successful treatment option in refractory pyoderma gangrenosum [39,40] , thus underlining its effectiveness in neutrophilic processes. The clinical course of ABD is mostly unpredictable, with possible relapses even despite adequate therapy.…”
Section: Case Reportmentioning
confidence: 98%
“…The effectiveness of infliximab for CD-associated PG is reported in many articles and abstracts [67,68,69,70,71,72,73,74,75,76]. Tan et al [74 ]reported the first promising results in 2 PG-associated CD patients.…”
Section: Treatmentmentioning
confidence: 99%